Parapatric speciation of Meiothermus in serpentinite-hosted aquifers in Oman - Munro-Ehrlich, Mason; Nothaft, Daniel B.; Fones, Elizabeth M.; Matter, Juerg M.; Templeton, Alexis S.; Boyd, Eric S. (Frontiers in Microbiology, 2023)
The factors that control the distribution and evolution of microbial life in subsurface environments remain enigmatic due to challenges associated with sampling fluids from discrete depth intervals via boreholes while avoiding mixing of fluids. Here, using an inflatable packer system, fracture waters were isolated and collected from three discrete depth intervals spanning >130 m in a borehole intersecting an ultramafic rock formation undergoing serpentinization in the Samail Ophiolite, Sultanate of Oman. Near surface aquifer waters were moderately reducing and had alkaline pH while deeper aquifer waters were reduced and had hyperalkaline pH, indicating extensive influence by serpentinization. Metagenomic sequencing and analysis of DNA from filtered biomass collected from discrete depth intervals revealed an abundance of aerobes in near surface waters and a greater proportion of anaerobes at depth. Yet the abundance of the putatively obligate aerobe, Meiothermus, increased with depth, providing an opportunity to evaluate the influence of chemical and spatial variation on its distribution and speciation. Two clades of Meiothermus metagenome assembled genomes (MAGs) were identified that correspond to surface and deep populations termed Types I (S) and II (D), respectively; both clades comprised an apparently Oman-specific lineage indicating a common ancestor. Type II (D) clade MAGs encoded fewer genes and were undergoing slower genome replication as inferred from read mapping. Further, single nucleotide variants (SNVs) and mobile genetic elements identified among MAGs revealed detectable, albeit limited, evidence for gene flow/recombination between spatially segregated Type I (S) and Type II (D) populations. Together, these observations indicate that chemical variation generated by serpentinization, combined with physical barriers that reduce/limit dispersal and gene flow, allowed for the parapatric speciation of Meiothermus in the Samail Ophiolite or a geologic precursor. Further, Meiothermus genomic data suggest that deep and shallow aquifer fluids in the Samail Ophiolite may mix over shorter time scales than has been previously estimated from geochemical data.